2005
DOI: 10.1080/08037050510034301
|View full text |Cite
|
Sign up to set email alerts
|

Stiffness index derived from digital volume pulse as a marker of target organ damage in untreated hypertension

Abstract: SIDVP, SI and DI were significantly correlated with target organ damage in untreated hypertension. However, only the SIDVP was independently associated with presence of vascular diseases. SIDVP simply derived from the DVP can be used as a marker for risk stratification in untreated hypertensive patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 22 publications
2
18
0
2
Order By: Relevance
“…Among the healthy subjects, Millasseau et al (2002) found that SI DVP correlated to PWV (r=0.65). Another study by Chen et al (2005) observed that among hypertensive subjects, SI DVP correlated to aortic SI (r=0.31) and distensibility (r=-0.34) measured via echocardiogram. Study by Woodman et al (2003) found that SI DVP correlated to PWV (r=0.54).…”
Section: Discussionmentioning
confidence: 92%
“…Among the healthy subjects, Millasseau et al (2002) found that SI DVP correlated to PWV (r=0.65). Another study by Chen et al (2005) observed that among hypertensive subjects, SI DVP correlated to aortic SI (r=0.31) and distensibility (r=-0.34) measured via echocardiogram. Study by Woodman et al (2003) found that SI DVP correlated to PWV (r=0.54).…”
Section: Discussionmentioning
confidence: 92%
“…The usefulness of the SI DVP as a noninvasive alternative to detect arterial stiffness was also successfully tested in patients with hypertension, diabetes mellitus and children [36,54,55] . Furthermore, SI DVP can help in the risk stratification of both hypertensive and apparently healthy people with different CV risk factors [56,57] .…”
Section: Discussionmentioning
confidence: 99%
“…Although no differences in age and HR were found, the mean BP was different between groups (Table VI in the online-only Data Supplement). Two arterial stiffness indices, stiffness index and compliance index, 20,21 were measured. Obese and overweight subjects showed trends toward higher stiffness index than normal weight subjects ( Figure 6C).…”
Section: Arterial Stiffening and Lower Lox Levels In Obese Humansmentioning
confidence: 99%